Rebranding for Excellence: Marketing Strategies of MAN PK at MAN 1 Yogyakarta - Azizah Fathur Rohiem; Zainal Arifin (Journal of Islamic Education Management Research, 2023)
Purpose  – This study explores the implementation of marketing strategies in managing an Islamic educational institution, explicitly focusing on MAN PK, the rebranded specialized program within MAN 1 Yogyakarta. Motivated by the competitive landscape influenced by globalization and the emergence of numerous Islamic educational institutions, the research aims to understand how marketing strategies enhance the quality and positioning of MAN PK. Design/methods/approach  – Conducted as qualitative research, this study employs observation, interviews, and documentation as data collection methods. The analysis includes transcript analysis, coding, grouping, comparing and contrasting, and data interpretation. Method triangulation and source triangulation are utilized for data validity. Findings  – The study's findings conclude that: 1) MAN PK, through a SWOT analysis, is positioned as a superior product within MAN 1 Yogyakarta, specializing in religious sciences and providing dormitory-based education. The existence of MAN PK contributes positively to the institution's image. 2) MAN 1 Yogyakarta's marketing strategy for MAN PK involves planning, market identification, segmentation, differentiation, and implementing the 7p marketing mix. This includes product, price, people, promotion, place, physical evidence, and process. 3) The rebranding of MAN PK at MAN 1 Yogyakarta results in enhanced program quality, evidenced by a strengthened dormitory-based curriculum, the production of high-quality graduates, and increased interest from prospective students. Research implications/limitations  – The research implies the significance of effective marketing strategies in shaping the image and quality of specialized educational programs. Limitations include the specific context of MAN 1 Yogyakarta, which may impact generalizability. Practical implications  – The findings provide practical insights for educational institutions aiming to enhance their programs through strategic marketing, particularly in specialization and rebranding. Originality/value  – This research contributes to the literature by thoroughly examining marketing strategies in the context of an Islamic educational institution, explicitly focusing on the rebranded program MAN PK within MAN 1 Yogyakarta. The study's originality lies in its specific focus on the marketing dynamics of a specialized program within a larger educational institution.